Health-Related Quality of Life Among Sickle Cell Anemia Patients: Examining the Predictability of Coping Styles and Social Support - Enyelunekpo Roberts; Keyna George; Kingsley Ekechi; Emmanuel Uye (Science: Indonesian Journal of Science, 2025)
Health-related quality of life (HRQoL) has remained a recurring issue when evaluating the effect of sickle cell anemia on individuals so affected. While studies have been conducted to determine the management of the disease with the use of physical and drug treatments, psychosocial factors tend to be limited. Therefore, this study examines the predictability of coping styles and social support on health-related quality of life (HRQoL) among individuals diagnosed with sickle cell anemia in selected hospitals and clinics in Port Harcourt, Rivers State, Nigeria. Cross-sectional survey design survey was adopted while data were collected from 200 participants using validated questionnaires. Data collected were analyzed using multiple regression to test one hypothesis which was accepted at p <.001 level of significance. The results showed that coping styles and social support jointly predicted HRQoL among study participants, R2= .372, F(3, 196) = 38.667, p <.001. Furthermore, coping style components of emotion-focused: β = .324, t = 5.062, p <.001; active coping: β = .251, t = 4.040, p <.001, and social support (β = .224, t = 3.506, p <.001) independently predicted HRQoL among study participants. The study concludes that coping styles and social support are robust predictors of HRQoL among sickle cell anemia in the study population. The study recommends that parents, government agencies and other stakeholders should proactively support sickle cell anemia patients with a social support system to manage their health situations to improve their overall quality of life.